Physician referral patterns and use of adjuvant therapy among patients with stage IB-IIIA non–small cell lung cancer (NSCLC) (2010-2017). Issue 28 (1st October 2022) - Kale, Hrishikesh; Wang, Wei-Jhih; Chirikov, Viktor; Shah, Anne; Apple, Jon
Abstract : 114 Background: As the treatment landscape for early-stage NSCLC continues to evolve with the recent approvals of targeted and immunotherapy agents in the adjuvant setting, it is important to understand physician referral patterns and predictors of adjuvant therapy (AT). This study examined physician referral patterns at key treatment phases and assessed predictors of receiving AT in stages IB-IIIA NSCLC patients. Methods: A retrospective study using the linked SEER-Medicare database (01/01/2010-12/31/2017) included patients newly diagnosed with stages IB-IIIA NSCLC who received surgical resection. Specialties were identified by linking NSCLC claims to AMA Physician Masterfile. AT was defined as the use of systemic chemotherapy or radiation therapy within 4 months of surgery. Multivariable logistic regression was conducted to assess predictors of receiving AT. Results: A total of 7, 108 patients met study criteria (53% IB; 9% IIA; 19% IIB; 20% IIIA). Primary care physician (PCP) (71%), surgical oncologist (29%), medical oncologist (36%) were the most frequently visited first specialist during pre-diagnosis, diagnosis to surgery, and post-surgery phases, respectively. The median time from diagnosis to surgery was 44 days. After surgery, 74% patients visited medical oncologist (62% IB; 87% IIA; 83% IIB; 88% IIIA). About 41% received AT (21% IB; 64% IIA; 56% IIB; 69% IIIA). Of those, the median time from surgery to adjuvant therapy was 46 days. Later stage at diagnosis and shorter referral time to medical oncologist significantly increased the odds of receiving AT (Table). Conclusions: The strongest predictors of receiving adjuvant therapy were time to medical oncologist post-surgery and stage at diagnosis. Future studies in the era of targeted therapies can use our results as a benchmark to optimize management and outcomes as well as assess changes in referral patterns in IB-IIIA NSCLC patients.Significant predictors of adjuvant therapy. Variable† Level Odds Ratio (95%CI) Time to medical oncologist visit (days) (Ref: No visit to medical oncologist) ≤ 23 5.343 (4.58 to 6.24)* 24 to 36 3.661 (3.13 to 4.28)* > 36 2.189 (1.87 to 2.56)* Age at diagnosis (years)(Ref: 66-70) 71-75 0.815 (0.71 to 0.94)* 76-80 0.509 (0.44 to 0.59)* 80+ 0.340 (0.28 to 0.41)* Cancer stage (Ref: Stage IB) IIA 5.212 (4.25 to 6.39)* IIB 3.775 (3.26 to 4.38)* IIIA 6.488 (5.56 to 7.57)* *P-value < 0.05.